Biodiversity, Ecosystem Functioning, and Services in Fresh Waters: Ecological and Evolutionary Implications of Climate Change - Woodward,G (Academic Press, 2015)
An Ecological and Evolutionary Perspective Andrea Belgrano, Guy Woodward, Ute Jacob ... Remarks References Biodiversity, Ecosystem Functioning, and Services in Fresh Waters: Ecological and Evolutionary Implications of Climate Change ...